Measuring the Sun's motion with stellar streams. Issue 1 (4th July 2017) - Malhan, Khyati; Ibata, Rodrigo A.
Abstract: We present a method for measuring the Sun's motion using the proper motions of Galactic halo star streams. The method relies on the fact that the motion of the stars perpendicular to a stream from a low-mass progenitor is close to zero when viewed from a non-rotating frame at rest with respect to the Galaxy, and that the deviation from zero is due to the reflex motion of the observer. The procedure we implement here has the advantage of being independent of the Galactic mass distribution. We run a suite of simulations to test the algorithm we have developed, and find that we can recover the input solar motion to good accuracy with data of the quality that will soon become available from the ESA/ Gaia mission.